Integrated sensor network for monitoring steel corrosion in concrete structures - José Enrique Ramón; José Manuel Gandía-Romero; Manuel Valcuende; Román Bataller (Vitruvio: International Journal of Architectural Technology and Sustainability)
Corrosion is one of the main triggering factors affecting the service life and durability of structures. Several methods are used for corrosion studies but electrochemical techniques are the most commonly applied. Corrosion processes monitoring and control by means of non-destructive techniques, such as the implementation of embedded sensors, has been the target of many works.  It is possible to obtain relevant information of structural corrosion processes in real time. This document describes a system including specific equipment and which allows obtaining relevant information about these corrosion processes. This system is formed by a sensor network. There are several types of electrodes, which are distributed throughout the structure under study and a specific equipment developed by the research group, which is used to determine pertinent parameters such as the corrosion potential (Ecorr) and the corrosion density (icorr) by applying sequences of potentiostatic pulses. The system allows to reliably determine the corrosion rate in different areas of the structure. The sensor, due to its configuration, provides information of a specific area of the structure, but on the other hand it is involved in the galvanic events that can occur along the structure by differential aeration, galvanic cells, etc. because the sensor is not isolated from the structure.  This system also procures information of buried and submerged elements. Besides, it is possible to obtain information related to temperature, concrete resistance. The system includes specific potentiometric sensors to monitor chloride access and carbonatation processes.